2007
DOI: 10.1007/s12013-007-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of electron transfer in photosystem II

Abstract: Photosystem II, being a constituent of light driven photosynthetic apparatus, is a highly organized pigment-protein-lipid complex. The arrangement of PSII active redox cofactors insures efficiency of electron transfer within it. Donation of electrons extracted from water by the oxygen evolving complex to plastoquinones requires an additional activation energy. In this paper we present theoretical discussion of the anharmonic fluctuations of the protein-lipid matrix of PSII and an experimental evidence showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 115 publications
(167 reference statements)
0
16
0
Order By: Relevance
“…The molecular mechanisms regulating photosynthetic ET have long been a subject of intensive studies but because of their complexicity it is still unclear how exactly the protein matrix exerts its control over the ET cofactors [3][4][5][6]. In particular, the role of NHFe, a very conservative component of the Q-type RCs, in photosynthetic charge separation and the temperature effects on ET between the two external quinone acceptors are among the most challenging issues [7,8]. Intriguingly, ET from reduced Q A to Q B is inhibited at temperatures below 200±20 K whereas Q A in RCs from various organisms remains fully active at cryogenic temperatures [9,10].…”
mentioning
confidence: 99%
“…The molecular mechanisms regulating photosynthetic ET have long been a subject of intensive studies but because of their complexicity it is still unclear how exactly the protein matrix exerts its control over the ET cofactors [3][4][5][6]. In particular, the role of NHFe, a very conservative component of the Q-type RCs, in photosynthetic charge separation and the temperature effects on ET between the two external quinone acceptors are among the most challenging issues [7,8]. Intriguingly, ET from reduced Q A to Q B is inhibited at temperatures below 200±20 K whereas Q A in RCs from various organisms remains fully active at cryogenic temperatures [9,10].…”
mentioning
confidence: 99%
“…b 559 being the trans-membrane component was suggested to be such a link. These data give the first direct evidence that the same collective motions influence the acceptor and the donor side via cytochrome b 559 [20,26]. This finding is even more important because if it is combined with results of the earlier studies, which have shown that the occurrence of the fast collective motion is necessary for the activation of electron transfer within the Q A -Fe-Q B complex [26][27][28][29], it suggests that cytochrome b 559 can play a role of coupler between the PSII donor and acceptor side.…”
Section: Resultsmentioning
confidence: 70%
“…Clearly, cyt. b 559 seems to play an important regulatory function on the oxidizing and reducing sides of PSII in addition to its importance for the PSII assembly and stability [7,26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Q A ubiquinone, bound to the M subunit, is in a hydrophobic area whereas the Q B ubiquinone, bound to the L subunit, is surrounded by charged and polar residues. The molecular mechanisms of the electron transfer between Q A and Q B ubiquinones have been a subject of challenging studies but the role of the NHFe, which is a very conservative component of RCs of the type II, in this process is still unknown [1,2]. Especially the role of NHFe in stabilization of the Q A and Q B binding sites and in the primary electron transfer (ET) is not clear.…”
Section: Introductionmentioning
confidence: 99%